2021
DOI: 10.3390/ijms22137081
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Molecules and Their Effect on the Molecular Mechanisms of Early Retinal Organoid Development

Abstract: Early in vivo embryonic retinal development is a well-documented and evolutionary conserved process. The specification towards eye development is temporally controlled by consecutive activation or inhibition of multiple key signaling pathways, such as the Wnt and hedgehog signaling pathways. Recently, with the use of retinal organoids, researchers aim to manipulate these pathways to achieve better human representative models for retinal development and disease. To achieve this, a plethora of different small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 268 publications
(282 reference statements)
0
20
0
Order By: Relevance
“…Germline deletion of BMP4 is embryologically lethal in mice between 6.5 and 9.5 days post conception [51] . Conditional deletion of BMP4 from the optic vesicle resulted in an optic cup devoid of neural retinal markers, indicating that BMP4 is required for retinal specification [52] . In vitro, BMP4 does not appear to be required for retinal differentiation, since the protocols without BMP4 also produce organoids.…”
Section: Discussionmentioning
confidence: 99%
“…Germline deletion of BMP4 is embryologically lethal in mice between 6.5 and 9.5 days post conception [51] . Conditional deletion of BMP4 from the optic vesicle resulted in an optic cup devoid of neural retinal markers, indicating that BMP4 is required for retinal specification [52] . In vitro, BMP4 does not appear to be required for retinal differentiation, since the protocols without BMP4 also produce organoids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Wnt, BMP, and IGF1, other factors should also be included in the system of regulation of the early retinal formation stages. It was found that FGF, TGFβ, Notch, Vax, retinoids, and Gas1 are responsible for the diversification and stabilization of the two major visual domains (RPE and NR) in the optic vesicles and eye cup [ 61 , 62 ]. The role of FGF and Wnt signaling has been studied in mice both during RPE and NR formation and in maintaining the properties of the retinal growth zone (ciliary margin (CM)).…”
Section: Embryonic Retina Self-organization In Vivomentioning
confidence: 99%
“…Along with studies of regulatory genetic networks, with the full complexity of this problem, attention is paid to epigenetic regulatory mechanisms, including the chromatin landscape, histone modifications, DNA methylation, non-encoded RNAs, etc. Thousands of enhancers are shown to be active in the developing retinae, and many of them have features of cell- and developmental stage-specific activity [ 23 , 62 , 92 , 93 , 94 ]. Attempts to identify the role of miRNAs were made earlier.…”
Section: Embryonic Retina Self-organization In Vivomentioning
confidence: 99%
“…Additionally, EPO binding to the EPOR/βcR heterodimer could activate Wingless (Wnt) signaling (Figure 1) [28], which could regulate cells survival, and differentiation. Wnt signaling is an important pathway responsible for the development of different ocular structure [29]. This heterodimer receptor contributes to the majority of the protective effects of EPO, which potentially underlines a vast quantity of therapeutic approaches.…”
Section: Heterodimer Isoform: Epor/βcrmentioning
confidence: 99%